Pediatric liver transplantation in Brazil over two decades: a scoping review - Julia Ribeiro Kormann; Kamila Recarcati; Mayara Mayer Alves; Ariel Pamela da Silva Lopes; José Sampaio-Neto; Izabel Cristina Meister Martins Coelho; Camila Aparecida Moraes Marques (Exploration of Digestive Diseases)
Brazil ranks second globally in absolute liver transplants and leads pediatric transplantation in Latin America. This scoping review aims to map the results and perspectives of pediatric liver transplantation in Brazil from 2000 to 2022. A scoping review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews Checklist (PRISMA-ScR) guidelines, using PubMed, Virtual Health Library (VHL), and ScienceDirect. From 293 records, 26 studies were included based on predefined criteria. The review focused on clinical indications, techniques, outcomes, and regional disparities. Results: Of the 26 included studies, 10 (38%) reported survival rates, showing 1-, 5-, and 10-year survival of 89.3%, 78.1%, and 68.5% for deceased donors and 93.1%, 85.7%, and 67.5% for living donors, respectively. Eleven studies (42%) discussed living donor liver transplantation (LDLT), which accounts for 53.4% of pediatric transplants. Eight studies (31%) detailed postoperative complications, such as vascular (up to 19%) and biliary (15.7%) issues, rejection (~ 50%), and infections. The COVID-19 pandemic led to a 20.6% reduction in transplant activity and increased waiting list mortality from 8.4% to 11.9%. Despite Brazil’s leadership in pediatric liver transplants, challenges persist, including donor shortages, diagnostic delays, geographic concentration in São Paulo (66%), and limited data systematization. These factors hinder equitable access and optimal outcomes across the country. To improve pediatric liver transplantation in Brazil, actions are needed to strengthen donor registration systems, decentralize services, enhance team training, and adopt techniques like split liver transplantation. Expanding national databases and prognostic tools will help address disparities and improve care.